2016
DOI: 10.1016/j.apenergy.2016.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Meeting renewable energy and land use objectives through public–private biomass supply partnerships

Abstract: Bioenergy is a significant source of renewable energy in the U.S. and internationally. We explore whether creation of localized bioenergy markets near existing military installations in the southeastern U.S. could simultaneously address military renewable energy generation objectives while reducing urban encroachment. We model the use of public-private partnerships to stimulate the creation of these markets, in which stable installation demand is paired with stable supply from surrounding landowners. We employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…PPP investment faces a series of opportunities and challenges in rural regions and the field of agricultural resource utilization [30][31][32][33]. Our investigation in the North China Plain found that there were many successful cases in the vast rural areas of using biogas and straw briquetting to improve the rural energy structure and control rural-related air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…PPP investment faces a series of opportunities and challenges in rural regions and the field of agricultural resource utilization [30][31][32][33]. Our investigation in the North China Plain found that there were many successful cases in the vast rural areas of using biogas and straw briquetting to improve the rural energy structure and control rural-related air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed simulations in cases where no innovation dynamics are present, have shown that policies that tackle this resource constraint can lead to significant increases in the industrial use of renewable resources [34,35]. Also public-private partnerships are helpful to create new supply chains of biomass [36].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Golecha and Gan developed an optimal contracting structure between biorefineries and biomass suppliers by finding the trade‐off between different components of biomass cost including farm‐gate cost, biomass transport, incentives to suppliers, nutrient replacement, and financial impact (loss) to the biorefinery due to inadequate biomass availability. In other studies, the impact of the biomass supply and farm participation rate on the performance of the biomass supply chain has also been investigated …”
Section: Introductionmentioning
confidence: 99%